The Influence Of Service Quality, Product Diversity And Price Discounts On Consumers' Interest To Buy Lova Collection In Bengkulu City - Jesica Lestari; Sri Ekowati (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of service quality, product diversity and price discounts on buying interest of consumers at the Lova Collection in Bengkulu City. This type of research is a type of quantitative descriptive research, the object of this research is the consumers of the Lova Collection in Bengkulu City, which is located on Jl. Lieutenant Suprapto, Kec. Ratu Samban, Bengkulu City, Bengkulu. The sampling method uses a non probability technique, namely accidental sampling. The number of respondents in this study were 160 people. Methods of data collection using a questionnaire. Data analysis techniques using Multiple Linear Regression Analysis Test, and Hypothesis Test, namely t test and f test.The results of this study can be concluded that the variable Service quality has a positive effect on Consumer Purchase Interest, product diversity has a positive effect on Consumer Purchase Interest, Price Discounts have a positive effect on Consumer Purchase Interest, and Service Quality, Product Diversity and Price Discounts together have a significant effect on Consumer Buying Interest in the Lova Collection in Bengkulu City.